Tinjauan Yuridis Tradisi Adat Uang Belis (Mahar) dalam Perkawinan Masyarakat di Desa Saga Kecamatan Detusoko Kabupaten Ende - Moi Wata Lexi Putra, Alexandri De Minggo (Faculty of Law, University of Dr. Soetomo, 2023)
The purpose of this research is to reveal the culture and meaning of belis money, marriage law regulations and the process of giving belis, and the consequences of the high price of belis. This research is a qualitative research. The location of this research is in Saga Village, Detusoko District, Ende Flores Regency, East Nusa Tenggara. The informants in this study were customary chiefs, Saga village heads and belis beneficiary women. Data was collected through interviews and observation. The results of this qualitative study indicate that the belis tradition still applies to the people of Saga village. Belis is not just a dowry in marriage, belis also has a function, namely as a condition for marriage, as a reflection of women's social status and as a change in the status and role of women in the family structure. However, belis is also the reason for violence against women in the household in Saga Village.